Modelling the Impact of Driver Work Environment on Driving Performance among Oil and Gas Heavy Vehicles: SEM-PLS - Al-Baraa Abdulrahman Al-Mekhlafi; Ahmad Shahrul Nizam Isha; Ali Nasser Al-Tahitah; Ahmed Farouk Kineber; Baker Nasser Saleh Al-Dhawi; Muhammad Ajmal (MDPI, 2024)
Indexed by WOS/Scopus/ERA